The Influence of Digital Payments, E-Commerce, and Financial Literacy on Revenue and the Quality of Accounting Information in SMEs - Kartikasari, Dyah Ayumurni; Ramadhanti, Wita; Kusuma, Poppy Dian Indira (EconBank: Journal of Economics and Banking, 2023)
This research aims to test and analyze the influence of perceived use of digital payments, ease of use of e-commerce, and financial literacy on perceptions of income and the quality of accounting information. The object of this research is the Getuk Goreng UKM located on Jalan Jendral Sudirman Sokaraja. A total of 30 MSMEs were taken as samples using purposive sampling. SEM-PLS has been used to analyze the data in this research. The results of this research indicate that perceptions of the use of digital payments and ease of use of e-commerce have no effect on income in Getuk Goreng SMEs. Financial literacy has a positive influence on income in Getuk Goreng SMEs. Income has a positive effect on the quality of financial reports in Getuk Goreng UKM. In this research, there are recent findings that income mediates between financial literacy and the Quality of accounting information